The project management tool kit : 100 tips and techniques for getting the job done right - Kendrick, Tom (AMACOM American Management Association, 2010)
The tools you need for success with every project!
Keywords: Project management -- Outlines, syllabi, etc.; elektronické knihy; electronic books